The ford foundation office for Viet nam and Thailand ( Opening Remarks by Charles R. Bailey Representative , ford foundation ) - Kỷ yếu hội thảo "Nâng cao chất lượng nghiên cứu và giảng dạy xã hội học đáp ứng yêu cầu của sự nghiệp công nghiệp hóa, hiện đại hóa đất nước" (Đại học Quốc gia Hà Nội, 2020)
The article introduces the National Sociology Workshop : " Enhancing the Quality of Sociology Training and Research , Meeting the Demands of National Industrialization and Modernization " Ha Noi , April 24 , 2001